Prevalence of and Influential Factors for Waterpipe Smoking among School-Attending Adolescents in Bissau, Guinea-Bissau - Jónína Einarsdóttir; Aladje Baldé; Zeca Jandi; Hamadou Boiro; Geir Gunnlaugsson (MDPI AG, 2024)
The marketing of sweetened and flavoured tobacco in the early 1990s resulted in an upsurge in waterpipe smoking (WPS), mainly among young people and women. Here, we estimate prevalence rates among school-attending adolescents aged 14-19 (girls 52%) for a lifetime experience of WPS and within the last 30 days (WPS < 30 days) and identify influential factors for such smoking in Bissau, Guinea-Bissau. A random sample (N = 2039) was drawn from a class-based register created for 16 schools in Bissau; attending students in June 2017 were invited to respond to a locally adapted Planet Youth questionnaire. Descriptive statistics, odds ratio with 95% confidence interval, and multinomial logistic regression analysis were used to identify influential factors for WPS. The prevalence rates for a lifetime experience of WPS and within < 30 days were high, 17.7% and 15.0%, respectively, with no significant gender difference. For both groups, a multinomial logistic regression analysis identified attending higher grades in school, use of alcohol and being a victim of sexual violence as significant, influential factors. The overlapping of influential factors suggests preventive work against substance abuse should focus on less stigmatising behaviour, such as WPS and firmer implementation of the Framework Convention of Tobacco Control (FCTC).